2005
DOI: 10.1128/aem.71.12.8881-8887.2005
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization of Glucooligosaccharide Oxidase from Acremonium strictum

Abstract: Glucooligosaccharide oxidase from Acremonium strictum was screened for potential applications in oligosaccharide acid production and carbohydrate detection. This protein is a unique covalent flavoenzyme which catalyzes the oxidation of a variety of carbohydrates with high selectivity for cello-and maltooligosaccharides. Kinetic measurements suggested that this enzyme possesses an open carbohydrate-binding groove, which is mainly composed of two glucosyl-binding subsites. The encoding gene was subsequently clon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
53
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(65 citation statements)
references
References 25 publications
(30 reference statements)
6
53
0
2
Order By: Relevance
“…In the case of glucooligosaccharide oxidase it is reported that replacement of His by various amino acids resulted in the isolation of proteins still bearing a covalently linked cofactor via the second site of attachment. However, not much information regarding the expression level and the spectral properties of these muteins was presented in these reports (5,6). For hexose oxidase from Chondrus crispus, which has been shown to be a bi-covalently flavinylated enzyme, spectral data indicative for the presence of a retained 6-S-cysteinyl linkage when replacing His with another amino acid are reported; however, the expression level is reduced from 3 g to ϳ50 mg for this mutein (6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of glucooligosaccharide oxidase it is reported that replacement of His by various amino acids resulted in the isolation of proteins still bearing a covalently linked cofactor via the second site of attachment. However, not much information regarding the expression level and the spectral properties of these muteins was presented in these reports (5,6). For hexose oxidase from Chondrus crispus, which has been shown to be a bi-covalently flavinylated enzyme, spectral data indicative for the presence of a retained 6-S-cysteinyl linkage when replacing His with another amino acid are reported; however, the expression level is reduced from 3 g to ϳ50 mg for this mutein (6).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have developed an expression system in Pichia pastoris that enabled us to obtain sufficient quantities of purified BBE from Eschscholzia californica, allowing a more detailed characterization. In the course of these studies it was discovered that BBE belongs to a novel group of flavoproteins containing a bi-covalently attached flavin cofactor (3)(4)(5)(6)(7).…”
Section: Berberine Bridge Enzyme (Bbe)mentioning
confidence: 99%
“…The Paraconiothyrium enzyme lacking heme in the protein is discriminated from CDH, 7,8) which contains heme. CBQ, 9,10) GOOX 11,12) and COX, 13) however, have similar properties; for instance, a molecular mass of 55 60 kDa, a broad substrate specificity, and the presence of FAD as a prothetic group. On the other hand, CDH and CBQ have similar amino acid sequences.…”
mentioning
confidence: 99%
“…Some enzymes have been known to oxidize lactose. Such enzymes, cellobiose dehydrogenases (EC 1.1.99.18, CDH), 7,8) cellobiose: quinone oxidoreductases (EC 1.1.5.1, CBQ), 9,10) glucooligosaccharides oxidases (GOOX), 11,12) and carbohydrate: acceptor oxidoreductase (COX), 13) however, have not been studied from a viewpoint of calcium lactobionate production in detail. This may be due to their instability at acidic pH, and or low specificity on O2 as an electron acceptor.…”
mentioning
confidence: 99%
“…2) Biological methods using bacteria [3][4][5][6][7][8] and fungi [9][10][11][12][13] have also been studied to produce LacA. However, these microorganisms have also not been applied for the production of LacA for foods, because they are not entirely suitable for industrial production from the perspective of food safety.…”
mentioning
confidence: 99%